Revision of Boolean Logical Models of Biological Regulatory Networks using Answer-Set Programming - Aleixo, Frederico Pinto (2022)
Biological regulatory networks are one of the most prominent tools used to represent complex, regulatory cellular processes. Creating computational models of these networks is key to better comprehend the corresponding cellular processes, as they allow for the reproduction of known behaviors, the testing of hypotheses, and the identification of predictions in silico. However, given that the process of constructing and revising such models is mainly a manual one, it is prone to error, and would therefore benefit from automation. An attempt at solving this problem has already been made using a mixture of Answer Set Programming (ASP) and C++. The previous attempt automated the process of revising these models, by using ASP to verify whether a Boolean logical model of a biological regulatory network was consistent with a given set of experimental observations and, in case of inconsistencies, used C++ to implement an algorithm capable of searching for possible sets of repair operations to render the model consistent. In our work we propose an alternative solution for this problem, a solution that fully leverages ASP which, being a declarative language tailored for this type of difficult search problems, has demonstrated to be a great tool to use both for consistency checking as well as model repair. This is in view of the fact that ASP offers a more intuitive and elaboration-tolerant programming style, which facilitates the processes of understanding, and modifying the code behind the model revision process. This, coupled with the powerful and exhaustively optimized solving capabilities provided by the state of the art ASP system clingo, has shown that there is great potential in adopting a fully ASP-based approach to aid in the automation of the revision of Boolean logical models. In this thesis we present the tool that we have developed to automate the process of revising Boolean logical models of Biological Regulatory Network(s) (BRN), which uses ASP to search for inconsistencies and perform repairs on these models.